Global Studies and Education in Developing Countries: Road-mapping Interdisciplinarity for Sustainable Development - Amodu, Akeem (Advances in Social Sciences Research Journal, 2021)
The education landscape in the 21st Century is witnessing global paradigm shifts. Emergent pedagogic practices are redefining hitherto compartmentalized systems of teaching and learning. With the advances in technology and the attendant expansions of the frontiers of knowledge - through the processes of digitalization and globalization -, the hitherto intellectual boundaries between disciplines are increasingly becoming blurred and of little or no relevance to contemporary scholarship. Emergent 21st century scholarship in the developed countries is characterized by a continued break down of intellectual barriers or walls between academic disciplines. A critical look at the courses being offered by academic institutions in the developed countries reflect interdisciplinarity: Global Studies; History and Philosophy of Sustainable Development (HPSD); and, History and Philosophy of Science (HPS) among others. A similar look at the curricular of most departments of higher institutions in developing countries however reveals holding on to traditional departmentalizations that characterized scholarship prior the commencement of the 21st century. With particular reference to the discipline Global Studies, we shall in this paper analytically discuss the emergent phenomenon of interdisciplinary scholarship as a means of road-mapping and repositioning academic departments and disciplines for sustainable development in developing countries. The paper argumentatively recommends frameworks for reforming the largely monodisciplinary education service delivery system in developing countries. In particular, the paper analytically asserts that interdisciplinarity has the potentials of engendering imperative solutions to the myriad of developmental challenges confronting developing nations across the globe.